Synthesis of Research on Mathematical Thinking Development under the Lesson Study and Open Approach Context - Jatuporn Nasinsroy; Maitree Inprasitha; Narumon Changsri (Randwick International of Education and Linguistics Science Journal, 2021)
The qualitative educational research synthesis of this paper is the incorporation of existing knowledge and the research results using Lesson Study and Open Approach innovations that relevant to the concern of students’ mathematical thinking development. The purpose of synthesis is to upsurge the generalization and pertinency of new knowledge development based on the results in incorporation the two innovations. Researchers employed document analysis to analyze the evidence of 266 postgraduate studies from the academic year 2003 to 2020. The research procedure consists of three stages. The results from the first stage showed that there are six research classifications identified, namely teacher and teaching, students and learning, assessment, classroom innovations, curriculum development, and educational policy. The research findings of the second phase indicated that there was a total of 210 studies (78.95%) were employing Open Approach incorporated in the Lesson Study process. Moreover, 53.33 percent are found in students and learning research classification. This is followed by 19.05 percent in teacher and teaching, 14.76 percent in classroom innovations, and 4.76 percent in assessment classifications. However, there was a limited of past postgraduate researchers interested to study curriculum development (4.29%) and educational policy (3.81%) research classifications. The findings of the final stage revealed that all the 210 postgraduate studies concerning the six research classifications are found to have different impacts on students’ mathematical thinking development. These effects occurred across a series of settings, synthesis approaches, expectations, and managing the Thailand Lesson Study Model.